HYPNOBIRTHING AS A THERAPEUTIC COMMUNICATION METHOD IN MOTHER AND CHILD HOSPITAL ANNISA PEKANBARU - Annisa Salsabila; Yustikasari (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research was conducted to find out why hypnobirthing is used as a therapeutic communication method, to find out how hypnobirthing is applied, and to find out the therapeutic communication model of RSIA Annisa. Using a qualitative method with a case study approach. Data collection techniques are through in-depth interviews, observation, literature study, and documentation. Data analysis techniques using flow model analysis. The results of the study, RSIA Annisa uses hypnobirthing as a therapeutic communication method to help pregnant women to manage stress, fear and anxiety during pregnancy so as to facilitate the delivery process. Starting from a concern for the welfare of mothers and children, RSIA Annisa builds personal relationships that result in psychologically fostered relationships in accordance with their motto "accompanying as close as a friend". Hypnobirthing is proven to change the mindset and make patients wiser in maintaining health during pregnancy. RSIA Annisa succeeded in creating effective therapeutic communication by prioritizing human relations skills, interpersonal communication, use of words / sentences, delivery methods and communication approaches tailored to the patient's background, good attitudes and ethics, and being a good listener. The conclusion of this study is that RSIA Annisa has successfully applied hypnobirthing as their therapeutic communication method in facilitating the labor process with a percentage of success reaching 80% to 90%.